Closed-Incision Negative Pressure Therapy Prevents Major Abdominal Donor-Site Complications in Autologous Breast Reconstruction. Issue 5 (9th November 2022) - Limpiado, MarcArthur; Guest, Rachel; Egan, Katie G.; Elver, Ashlie A.; Johnson, Braden M.; Cullom, Melissa E.; Nazir, Niaman; Holding, Julie; Lai, Eric C.; Butterworth, James A.
Abstract : Background: Outcomes in autologous breast reconstruction continue to improve with refinements in microsurgical techniques; however, donor-site morbidity remains a concern. Closed-incision negative pressure therapy (ciNPT) has been shown to reduce wound complications. Limited evaluation in abdominal donor sites has shown promising results. We hypothesize that ciNPT will reduce abdominal donor-site complications. Methods: A retrospective chart review was performed of patients who underwent abdominally based autologous free tissue transfer for breast reconstruction by 4 microsurgeons at an academic institution from 2015 to 2020. The application of a commercial ciNPT for donor-site management was at the discretion of the operating surgeon. Demographics, operative details, and management of donor-site complications were analyzed. Results: Four hundred thirty-three patients underwent autologous breast reconstruction; 212 abdominal donor sites were managed with ciNPT and 219 with standard dressings. Demographics were statistically similar between groups. Abdominal wound healing complications were noted in 30.2% of ciNPT patients (64/212) and 22.8% of control patients (50/219, P = 0.08); however, overall wound complications were attributed to obesity on multivariable analysis. Closed-incision negative pressure therapy significantly decreased complications requiring reoperation (ciNPT 6.2%, 4/64; control 26.5%, 13/51; P = 0.004). There were no significant differences in surgical site infection rates ( P = 0.73) and rates of abdominal scar revisions (ciNPT 11.8%, 25/212; control 9.1%, 20/219; P = 0.37). Conclusions: Use of ciNPT in abdominal donor-site management significantly decreases the incidence of delayed wound healing requiring surgical intervention, with one major wound healing complication prevented for every 6 donor sites managed with ciNPT.